Seed germination of two medicinal plants: Desmodium pulchellum (L.) Benth. and D. Triflorum (L.) DC. - Rahman, Md. Zahidur; Rahman, M. Oliur; Hassan, Md. Abul (Bangladesh Journal of Plant Taxonomy, 2012)
DOI: http://dx.doi.org/10.3329/bjpt.v19i2.13138 Bangladesh J. Plant Taxon. 19(2): 209-212, 2012 (December)